STUDI EKSPERIMEN VORTEX INDUCED VIBRATION ENERGY CONVERTER (VIVEC) PADA REYNOLDS NUMBER 50.000 - Karina Putri Nurma Gumpita; Setyo Nugroho; Raden Sanggar Dewanto (PROSIDING SNAST, 2018)
Hydro energy is one of the largest sources and capale generating 16% of electricity in the world. In Indonesia, In Indonesia, the potential of hydro energy reaches 75 GW. However, currently only about 9% of it that has been utilized properly. Vortex-Induced Vibration Energy Converter (VIVEC) is one technology that utilizes hydro energy. VIVEC converts the translational motion up and down from a cylinder attached to a slider into electrical energy. The oscillation of the cylinder is caused by the release of the vortex that forms around the cylinder when it hit by water at a certain speed. VIVEC has big potential to applied in Indonesia. This is because most of river in Indonesia has stable debit. One of them is Sungai Citarum. Sungai Citarum is at Desa Dayeuh Kolot, Kabupaten Bandung, Jawa Barat has max debit 397,4 m3/sand min debit 204,1 m3/s. One of the parameters affect the performance of VIVEC is Reynolds Number. This research focused on Reynolds Number around 50.000 with physical test using towing tank. The parameters as same as parameters at Sungai Citarum, which is velocity 0,4 m/s and the diameter of cylinder is 0,1257 cm. Based on this research, maximum amplitudo is 4,43 cm, frequency of oscillating is 0,67, and the efficiency of VIVEC is 13,03%.